Time-dependent mood fluctuations in Antarctic personnel: a meta-analysis. (28th September 2017) - Hawkes, Clare; Norris, Kimberley
ABSTRACT: The third-quarter phenomenon is the dominant theoretical model to explain the psychological impacts of deployment in Antarctica on personnel. It posits that detrimental symptoms to functioning, such as negative mood, increase gradually throughout deployment and peak at the third-quarter point, regardless of overall deployment length. However, there is equivocal support for the model. The current meta-analysis included data from 21 studies (involving 1, 826 participants) measuring negative mood during deployment to elucidate this discrepancy. Across studies analyses were conducted on three data types: stratified by month using repeated-measured all time points meta-analytic techniques and pre/post-deployment data for summer/winter deployment seasons. Our results did not support the proposed parameters of the third-quarter phenomenon, as negative mood did not peak at the third-quarter point (August/September) of deployment. Overall effect sizes indicated that negative mood was greater at baseline than the end of deployment for summer and winter deployment seasons. These findings have theoretical and practical implications and should be used to guide future research, assisting in the development and modification of pre-existing prevention and intervention programmes to improve well-being and functioning of personnel during Antarctic deployment.